Given f(x) = 2x² – 3 and g(x) = x + 1 determine g(f(3)​

Question

Given f(x) = 2x² – 3 and g(x) = x + 1 determine g(f(3)​

in progress 0
Helga 7 months 2021-07-30T07:47:14+00:00 1 Answers 6 views 0

Answers ( )

    0
    2021-07-30T07:48:18+00:00

    Answer:

    g(f(3)) = 16

    Step-by-step explanation:

    Step 1: Define

    f(x) = 2x² – 3

    g(x) = x + 1

    f(3) = x = 3

    Step 2: Find f(3)

    f(3) = 2(3)² – 3

    f(3) = 2(9) – 3

    f(3) = 18 – 3

    f(3) = 15

    Step 3: Find g(15)

    g(15) = 15 + 1

    g(15) = 16

    g(f(3)) = 16

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )